Science education and science communication by online interaction - Nobre, Alexandra (2014)
Science Education and Science Communication to the gereral public have been internationally recognized as mandatory measures, in order to promote the scientific literacy of society in general. Indeed, the sustainability of our planet relies on the responsible behaviors and wise decisions of informed citizens. In the particular case of this work, the authors are concerned with the promotion of scientific literacy in Portugal and use different strategies, from face to face events to online interactions. In this particular case, the projects involve the coordination of structured web pages, as well as the administration of pages on Facebook. In each case the visiting public, the time dispensed on searching and the deepness of the response expected, mirrors different public expectations. One of the projects is “Ciencia com Todos” (CcT) (Science with everyone) that, although mainly directed for a younger public attending the different education levels, allows any citizen to clarify its doubts on scientific contents, either related to everyday life or to more deep subjects. In fact, all questions are answered by a scientific commission comprising 202 elements that cover all areas, from natural sciences (biology, chemistry, geology, physics and mathematics ) to the medicine and even social sciences and humanities (psychology, archeology, sociology, history, geography, mathematics education, history and philosophy of sciences). Moreover, the web site has another section where science articles written by the collaborators and scientific commission are published regularly. No matter the format (answers or texts), there is always the concern of using an easy and understandable language, accessible to the general public, without losing scientific rigor and accuracy. Another project is “Science Through Our Lives” (STOL) with a wide vision of science and art, that has a page on Facebook with an average of 3.000 visits per week and that publishes posts on science senso lato, on a regular basis.